The effect of improved metabolic risk factors and metformin therapy on circulating hepatokines in obese, insulin-resistant adolescents - Kılınç, Suna; Kırankaya, Ayşegül; Atay, Zeynep (Karger, 2019)
Introduction: The molecular mechanisms underlying insulin resistance (IR) is complex and has not been fully elucidated yet. The experimental studies point out the role of liver-derived proteins, called hepatokines. Aims: To compare metabolic parameters and hepatokines levels in obese adolescents and healthy controls and to assess the effect of metformin therapy on plasma hepatokines levels in obese, insulin-resistant adolescents. Material and Methods: Sixty-nine subjects (38 girls, 31 boys) aged between 12-18 years were included. Participants were categorized into two groups. The first-group comprised obese adolescents with a body mass index (BMI) >95th percentile and the second-group comprised healthy controls with a BMI between the 5th and 85th percentile. Anthropometric and biochemical (glucose, insulin, lipid profile, Fetuin-A, fibroblast growth factor-21 (FGF-21), angiopoietin-related growth factor (AGF), leukocyte-derived chemotaxin 2 (LECT2) and Selenoprotein-P (SEPP1)) parameters were evaluated. Firstly, metabolic parameters and hepatokines levels were compared in obese group and healthy controls. Secondly all obese patients underwent a standard oral glucose tolerance test (OGTT). Patients diagnosed with IR at OGTT were started metformin (2g/day, 2 doses) therapy for 6-months. Then the differences in the biochemical characteristics and hepatokines levels analyzed between pre- and post-treatment. Plasma hepatokines levels were determined using an enzyme-linked immunosorbent assay (ELISA) method (Abbkine, Inc. China). Results: Study included 44 obese (21 males, 23 females; mean age: 13.1±1.9 years) and 25 healthy non-obese children (10 males, 15 females; mean age: 13.5±1.9 years). Glucose, insulin, HbA1c, Fetuin-A, LECT2 and SEPP1 levels were significantly higher in obese patients (P<0.05); FGF-21 and AGF levels were not significantly different between the two groups (P=0.776, P=0.214). There was a statistically significant decrease in serum glucose, insulin, HbA1c, total cholesterol, triglyceride and LECT2 levels and a statistically significant increase in serum HDL-cholesterol levels after 6-months of metformin therapy. There was no statistically significant difference in Fetuian-A, FGF-21, AGF and SEPP1 levels after treatment (P>0.05). Conclusion: Plasma levels of Fetuin-A, LECT2 and SEPP1, which are thought to be effective in insulin signaling pathways, were significantly higher in obese patients. Six-months of metformin therapy also found to be effective in decreasing serum LECT2 levels.
Keywords: Childhood-Obesity; Insulin Resistance; Metformin; Hepatokines; Fetuin-A; EGF21; AGF,LECT2; SEPP1